Вплив спортивного орієнтування та туризму на рекреаційну складову працівників силових структур - Лаврентьєв, Олександр Миколайович; Головащенко, Роман Володимирович; Деркач, Оксана Вікторівна; Буток, Олена Володимирівна; Рома Головащенко; Олександр Лаврентьєв (Науковий часопис Українського державного університету імені Михайла Драгоманова, 2023)
У статті розкриваються питання рекреаційних заходів, щодо відновлення працездатності працівників силових структур засобами спортивного орієнтування та туризму. Які за своїм змістом вирішують питання пов’язані з відтворенням фізичних, інтелектуальних та емоційних здібностей працівників. Спортивне орієнтування та туризм за своєю специфікою можуть вирішувати питання військово-прикладного (характеру) виду спорту. Спортивне орієнтування під час рекраційних заходів може проводитись засобами будь-якої гри або розваги направлених на розвиток уваги, просторової памяті та фізичних якостей. Туризм повинен відбуватись на лоні природи і мати декілька напрямів роботи це: звичайні піші походи або походи за складними маршрутами, біг по пересічній місцевості (шоссе, ліс та лісопарки), стрибки, спортивна ходьба тощо. Завдяки своїй доступності у застосуванні дані види рекреації є розповсюдженими та актуальними серед населення та можуть використовуватись праціниками силових структур. Рекреація із використанням спортивного орієнтування та туризму відрізняється тим, що хворий (поранений) безпосередньо сам приймає участь в своєму відновленні із використанням фізичних вправ. Поступово за рекомендаціями інструктора ЛФК збільшується інтенсивність і навантаження, адаптуючи хворого до повноцінного життя. Дані засоби направлені на перебудову організму працівників силових структур, на можливість їх активної діяльності за різних умов, характеру і змін навколишнього середовища, що направлено на вітворення і збереження професійних здібностей, дозволить краще переносити кліматичні негаразди та забезпечить профілактику та швидке відновлелення після захворювань (поранень) тощо.

In the development of sports orientation and tourism, two trends are clearly visible: the first is the development of mass forms of activities that are purely health-oriented. The second is to improve the training system and increase the skills of highly qualified athletes. The professional skills of these sports are necessary both in wartime and in peacetime. For teachers, military personnel, biologists, geographers, physicists and many other specialists, it can become an applied sport, as it allows you to successfully solve a number of issues. They help to act both individually and in a team. The article discusses the issue of recreational activities, in order to restore the working capacity of employees of the security forces by means of sports orientation and tourism. Which, in their content, solve issues related to the reproduction of physical, intellectual and emotional abilities of employees. Sports orientation and tourism, by their specificity, can solve the issue of the military-applied (character) type of sport. Sports orientation during recreational activities can be carried out by means of any game or entertainment aimed at developing attention, spatial memory using a map and compass, overcoming a certain route on unfamiliar terrain through control points fixed on the map and terrain, the ability to think productively and make decisions against the background of developing fatigue and the development of physical and willpower qualities. Tourism should take place in the bosom of nature and have several directions of work, that is: ordinary hiking or by means of complex routes, running on a flat surface and in the forest, jumping, sports walking, etc. Due to their accessibility in application, these types of recreation are widespread and relevant among the population and can be used by employees of law enforcement agencies. Recreation using sports orientation and tourism differs in that the patient (wounded) directly participates in his recovery using physical exercises. Gradually, according to the instructor's recommendations, physical therapy increases the intensity and load, adapting the patient to a normal life. These funds will be directed to the reorganization of the body of the employees of the power structures, which will ensure the possibility of their active activity under various conditions of the nature and changes of the environment, which is aimed at the reproduction and preservation of professional abilities, will allow to better tolerate climatic adversities and will provide prevention against diseases (injuries), etc.
The influence of sports orientation and tourism on the recreational component of employees of military structures
Keywords: спортивне орієнтування; туризм; військовослужбовець; працівник; правоохоронні органи; фізична підготовка; рекреація; sports orientation; tourism; military serviceman; employee; law enforcement agencies; physical training; recreation